Does treatment quality matter?: multilevel examination of the effects of intervention quality on recidivism of adolescents completing long‐term juvenile justice residential placement - Baglivio, Michael T. (Criminology & public policy, 2018)
The Florida Department of Juvenile Justice has implemented a process to evaluate the treatment quality of interventions provided statewide in all long‐term residential programs. In the current study, we examine the predictive validity of this treatment quality component in the prediction of recidivism of youth (N = 2,397) who completed juvenile justice residential programs from July 1, 2013 to June 30, 2014. We use hierarchical linear modeling to assess the effects of treatment quality (as youth are nested within programs), controlling for demographic and criminal history factors. The results indicate that higher average treatment quality scores of interventions received within a residential program decreased the likelihood of subsequent arrest, conviction, and reincarceration, whereas the highest treatment quality score of any specific intervention provided within the program decreased the odds of reincarceration only.